2013
DOI: 10.1002/oby.20350
|View full text |Cite
|
Sign up to set email alerts
|

Effects of risperidone on energy balance in female C57BL/6J mice

Abstract: Objective To investigate the effect of risperidone on energy expenditure and weight gain in female C57BL/6J mice. Design and Methods Body weight and composition, food intake, energy expenditure, and activity were determined weekly. mRNA expression of uncoupling protein 1 in brown adipose tissue, orexin and brain-derived neurotrophic factor in the hypothalamus were quantified by Real-Time PCR. Results Risperidone tended to induce a greater body weight gain (P=0.052) and significantly higher food intake (P=0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
3
12
0
Order By: Relevance
“…This was in addition to hyperphagia and weight gain. Recently, Li et al (48) showed that resting EE was higher in similarly dosed mice. Similar to our finding of reduced wheel activity (Figure 2), the authors found fewer x,y beam breaks over their 3-week study and elevated Ucp1 expression in the BAT of their mice (48).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This was in addition to hyperphagia and weight gain. Recently, Li et al (48) showed that resting EE was higher in similarly dosed mice. Similar to our finding of reduced wheel activity (Figure 2), the authors found fewer x,y beam breaks over their 3-week study and elevated Ucp1 expression in the BAT of their mice (48).…”
Section: Discussionmentioning
confidence: 97%
“…Recently, Li et al (48) showed that resting EE was higher in similarly dosed mice. Similar to our finding of reduced wheel activity (Figure 2), the authors found fewer x,y beam breaks over their 3-week study and elevated Ucp1 expression in the BAT of their mice (48). We did not observe weight gain or hyperphagia in our mice, which could in part be due to the lower dose used in our study (0.75 mg/kg once daily by oral gavage) compared to that above (47,48).…”
Section: Discussionmentioning
confidence: 97%
“…Mechanisms for this weight gain are unclear. Despite the weight gain effect being widely presumed to be related to hyperphagia , other animal studies have also shown that a transient increase in appetite is accompanied by decreased energy expenditure and decreased thermogenic activity in brown adipose tissue . Interestingly, McCracken et al .…”
Section: Discussionmentioning
confidence: 99%
“…Nine weeks of risperidone treatment led to a 2.5 g increase in body weight (Figure 3-6A, p < 0.05). Food intake behavior for C57BL/6J mice was found to be similar between groups, resulting in normal daily caloric ingestion, as reported previously for risperidone (Figure 3-6B) [215][216][217][218] . Similarly, risperidone treatment had no effect on digestive efficiency (Figure 3-6C).…”
Section: Expendituresupporting
confidence: 83%
“…However, the undoubetly multifactorial nature of the cardiometabolic effects is not completely understood, and patients still suffer from the side effects of weight gain. In humans, risperidone may promote weight gain through appetite stimulation, although many animal studies comparing SGAs challenge this hypothesis [215][216][217][218] . Risperidone-induced weight gain is believed to be multifaceted, involving genetic, metabolic, and environmental contributors 219,220 .…”
Section: Introductionmentioning
confidence: 99%